Macroeconomic fluctuations in a small open economy of Malaysia / Liew San Yee - Liew , San Yee (2021)
This thesis examines the sources of macroeconomic fluctuations in a small open economy of Malaysia by utilizing a dynamic stochastic general equilibrium model (DSGE) based on the New Keynesian framework. The model incorporates various features such as external habit formation, internal investment adjustment cost, variable capacity utilization, domestically produced goods prices and wages stickiness, incomplete exchange rate pass-through, and financial accelerator. The model is log-linearized, parameters are estimated with Bayesian techniques, calibrated, and simulated and subjected to several exogenous shocks. The dynamic movements of key macroeconomic variables in response to these disturbances are analyzed using the impulse response functions and the sources of macroeconomic fluctuations are examined through the variance decomposition. The results from the variance decomposition show analysis indicate that, both monetary policy shock and technology shock are the main driving forces of macroeconomic fluctuations of the real sector’s variables (output, consumption, investment) and nominal variables (inflation, nominal interest rates, real exchange rate). The results also suggest that domestic shocks play a more significant role as sources of macroeconomic fluctuations in the model than do foreign shocks.